Lugares adonde no quiero regresar - Polo, Higinio ([Vilassar de Dalt (Spain)] : El Viejo Topo, 2018)
A trip to cities which have been destroyed by war.
Online resource; title from PDF title page (Digitalia, viewed May 25, 2019)
Keywords: Polo, Higinio -- Travels; Extinct cities; Electronic books